Heavy metal pollution and co-selection for antibiotic resistance: A microbial palaeontology approach. (November 2019) - Dickinson, A.W.; Power, A.; Hansen, M.G.; Brandt, K.K.; Piliposian, G.; Appleby, P.; O'Neill, P.A.; Jones, R.T.; Sierocinski, P.; Koskella, B.; Vos, M.
Abstract: Frequent and persistent heavy metal pollution has profound effects on the composition and activity of microbial communities. Heavy metals select for metal resistance but can also co-select for resistance to antibiotics, which is a global health concern. We here document metal concentration, metal resistance and antibiotic resistance along a sediment archive from a pond in the North West of the United Kingdom covering over a century of anthropogenic pollution. We specifically focus on zinc, as it is a ubiquitous and toxic metal contaminant known to co-select for antibiotic resistance, to assess the impact of temporal variation in heavy metal pollution on microbial community diversity and to quantify the selection effects of differential heavy metal exposure on antibiotic resistance. Zinc concentration and bioavailability was found to vary over the core, likely reflecting increased industrialisation around the middle of the 20th century. Zinc concentration had a significant effect on bacterial community composition, as revealed by a positive correlation between the level of zinc tolerance in culturable bacteria and zinc concentration. The proportion of zinc resistant isolates was also positively correlated with resistance to three clinically relevant antibiotics (oxacillin, cefotaxime and trimethoprim). The abundance of the class 1 integron-integrase gene, intI1, marker for anthropogenic pollutants correlated with the prevalence of zinc- and cefotaxime resistance but not with oxacillin and trimethoprim resistance. Our microbial palaeontology approach reveals that metal-contaminated sediments from depths that pre-date the use of antibiotics were enriched in antibiotic resistant bacteria, demonstrating the pervasive effects of metal-antibiotic co-selection in the environment. Graphical abstract: Unlabelled Image Highlights: A sediment core provides a window into historical metal pollution. Bacteria could be isolated from this temporal gradient. Bacterial zinc resistance correlates with zinc concentration. Zinc resistance positively correlates with antibiotic resistance. Antibiotic resistant isolates occur before the clinical use of the same antibiotic.